Teachers’ perceptions on the use of whatsapp groups during virtual classes to teach English as a foreign language in a public school from Latacunga. - Pullupaxi Tamayo, Febe Paola (2023)
During the covid 19 – pandemic, technology has increased their effect in education. Teachers and students were forced to change the traditional modality to conduct the classes in a virtual way. They had to use technological tools to maintain the communication via online. WhatsApp was considered as an app that supported the teaching English process in virtual classes. That is why the aim of this investigation is to determine teachers' perceptions on the use of WhatsApp in virtual classes to teach English as a foreign language in a public school from Latacunga. This investigation used a qualitative method. The research design was descriptive research. This study used an open interview that was applied to two teachers. To analyze the data, the researchers used thematic analysis. The results showed that WhatsApp had some advantages and disadvantages in the use of a pedagogical support in English language teaching. The advantages showed that WhatsApp served as a tool for communication between teacher and student. This app also allowed teachers to send assignments, links, teaching material and learning guides that students needed to do their work autonomously. This was of great help because the students who cannot connect to classes virtually through zoom can have access to the material and had the opportunity to work at home. On the other hand, the disadvantages showed that WhatsApp didn’t become an effective English teaching-learning tool because it was not used in the appropriate way in order to develop English skills. The use of WhatsApp was focused purely on transmitting information and not to practice the skills. It is because the teachers didn't apply methodology correctly in a virtual mode. There were no activities to promote an interaction orally or written through WhatsApp and developing student's learning. Finally, accessibility was also a disadvantage, as many students could not connect to the classes as they did not have Internet or mobile devices which affects the performance of students in classes. Then, it is concluded that WhatsApp in this research was a useful tool to have quick communication between the teacher and the student to send resources. However, this tool was not used to develop and practice English Skills.